If the Shoe Fits: Proposing a Randomised Control Trial on the effect of a digitised in-custody footwear technology compared to a paper-based footwear method. (Crime, Security and Society, 2018)
In order to address the issue of footwear capture from individuals arrested for recordable crime, technology has been developed, which is known as Tread Finder. This technology and development was made possible through Home Office Police Innovation Funding. Tread Finder is now a finished product and the technology has been deployed into a North London custody suite. Tread Finder incorporates the use of a 300 dpi scanner and newly developed software enabling capture, assisted coding and automated geographical crime scene searching. This paper sets out the proposal of a Randomised Control Trial to replicate and upscale a previous lab based experiment into a field environment to assess the cost, efficiency and crime solving benefits realised as a result of deploying Tread Finder technology compared with the previous paper based alternative.